Comparative outcomes of proximal femur intramedullary nailing vs. cemented bipolar hemiarthroplasty for treating intertrochanteric fractures in patients aged 75 and older: analysis of risk factors for postoperative all-cause mortality - Yan Deng; Xiang-Ping Zhou; Bin Sun; Guo-Hui Li; Zuo-Ming Tong (BMC Surgery)
Abstract Background As the population continues to age, the occurrence of intertrochanteric femoral fractures (IFFs) has steadily increased. The main aims of this investigation were to evaluate and compare the clinical outcomes, ambulatory ability, overall survival, and all-cause mortality between two cephalic screws combined with compression proximal-femoral intramedullary nailing internal fixation (IF) and long-stemmed cemented bipolar hemiarthroplasty (LCHA) in patients aged 75 years and older. The secondary objective was to investigate the relative independent risk factors contributing to postoperative all-cause mortality. Methods A retrospective analysis was conducted on 251 elderly patients with IFF who underwent IF or LCHA between January 2018 and October 2022. We employed generalized estimation equations along with univariate and multivariate analyses to examine the impact of various surgical interventions and other pertinent factors on postoperative ambulatory ability and all-cause mortality outcomes. Associations between sex, age, number of comorbidities, aspartate aminotransferase (AST) levels, total blood transfusions, and mortality were analyzed via Cox proportional hazards models. Results The analysis included a cohort of 120 patients from the IF group and 121 patients from the LCHA group. Statistically significant differences were not observed in the clinical outcomes, ambulatory ability, overall survival, or all-cause mortality after surgical treatment between the groups receiving IF and LCHA (p > 0.05). Nevertheless, among patients aged ≥ 85 years, the IF group demonstrated a lower rate of all-cause mortality than the LCHA group did (p < 0.05). As age increases and the number of preoperative comorbidities and the amount of perioperative transfusion increase, the preoperative AST level decreases, which is associated with a greater risk of postoperative death. (p < 0.05). Conclusions In elderly patients aged 75–84 years with intertrochanteric femur fractures, both internal fixation (IF) and long-stemmed cemented hemiarthroplasty (LCHA) are viable treatment options. However, for patients aged 85 years and older, IF is associated with a relatively lower postoperative all-cause mortality rate and should be prioritized as a treatment modality. Additionally, preoperative AST levels may serve as a valuable predictor of postoperative all-cause mortality in elderly patients undergoing surgery for intertrochanteric femur fractures.